Performance Evaluation of a Hybrid Solar Panel and Thermoelectric Generator (TEG) System with Copper Plate Enhancement on the Hot Side - Bayusari, Ike; Ronting, Virgie Claudia; Soraya, Ayu; Caroline; Hermawati; Rahmawati (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2025)
The utilization of solar energy is commonly achieved through solar panels; however, heat dissipation from the panels often reduces their overall efficiency. A hybrid system combining solar panels and thermoelectric generators (TEGs) offers a potential solution to this issue. To enhance the temperature difference (∆T) across the TEG, a metal plate can be added to the hot side, while a heatsink is applied to the cold side. This study investigates the performance of three prototype configurations: a 2.4 Wp monocrystalline solar panel integrated with a TEG module, with variations in the addition of a copper plate, an aluminum plate, and no plate on the TEG hot side. Experimental results demonstrate that the prototype with a copper plate yielded the highest average values, with a ∆T of 8.63 °C, voltage of 11.57 V, current of 0.17 A, and power output of 2.02 W. In comparison, the aluminum plate prototype achieved a ∆T of 6.11 °C, voltage of 11.57 V, current of 0.16 A, and power output of 1.71 W, while the prototype without any plate produced a ∆T of 5.80 °C, voltage of 10.79 V, current of 0.15 A, and power output of 1.63 W. Among all tested configurations, the copper plate prototype exhibited superior performance, attributed to the high thermal conductivity of copper, which significantly enhances the ∆T across the TEG, thereby increasing electrical output.